EVALUASI KINERJA JALAN NASIONAL TERHADAP KARAKTERISTIK LALU LINTAS PADA RUAS JALAN NASIONAL KOTA PALEMBANG - Sartika Nisumanti; Evina Krisna (Jurnal Tekno Global, 2020)
The roads transportation is an important infrastructure as one of the land transportation infrastructures for the movement of social activities and to support economic development, specifically in Palembang City. The population growth of Palembang City has resulted in an increase in the number of vehicles and highway users. As a result, transportation activities in Palembang, especially at Parameswara roads are increasing. The impact of this, there will be heavy traffic volume, resulting in conflicts on the road, which lead to traffic accidents. Therefore, there will be congestion and a decrease in the performance of the road speed.The research is conducted at Parameswara Road in Palembang that visually diminished the ability to accommodate the road traffic volume per day, accordingly the effect of traffic that occurs due to the lack of road capacity as the sequence of large volume traffic. The purpose of this study is to determine the capacity and level of road services to carried out the performance value on this road. The method used in the analysis is the Greenshield model, Greenberg, and Underwood. This study explains the maximum volume at peak hour that develop on Monday is between 1561 smp/hour and 1549 smp/hour. Whereas the lowest is around 1225 smp/hour and 1008 smp/hour that occurs on Sunday. Therefore, the analysis of service level on the research years at Parameswara Road depicts the saturated traffic conditions and low starting speed with D service index category and service level analysis at 10 years of planning time projections, the lpda result is from 2022 to 2026, The Parameswara road conditions at E and F service index categories are the traffic jam circumstances and slight speed. Hence, it necessitates constructing a non-plot way at Parameswara Road intersection to tackle this traffic congestion.Keywords: Greenshield, Greenberg, Underwood, Road Capacity.